Music in Elementary Education: National Journal References Published between 2000 and 2010 in Brazil (Per Musi, 2017)
This article bring out results of a masters’ research developed in the Post Graduation Program in Music at the Universidade Federal de Goiás (Federal University of Goiás), which goal was to identify and analyze the concepts that underlie the prevailing thought in publications in national journals about music education in basic education from 2000 to 2010. The complex thinking from the perspective of Edgar Morin and the language concepts of Mikhail Bakhtin complements the theoretical referece from the research. Therefore, we bring in this article data and reflections from the results obtained in the research, with focus on the theoretical references from the analyzed articles. Among the results, it is observed that the area of music education in the field of basic education interacts with other areas and fields of knowledge in the construction of theoretical references for the discussion of its particularities in the context of basic education, data that corroborates to the results of other researches. It is noted that in some aticles, authors from specific area (musical education) are taken as central in their discussions. It is also noted, that laws and regulatory documents compose and thematize the speech about musical education in basic education.